Higher-Ordered Actin Structures Remodeled by Arabidopsis ACTIN-DEPOLYMERIZING FACTOR5 Are Important for Pollen Germination and Pollen Tube Growth - Zhu, Jingen; Nan, Qiong; Qin, Tao; Qian, Dong; Mao, Tonglin; Yuan, Shunjie; Wu, Xiaorong; Niu, Yue; Bai, Qifeng; An, Lizhe; Xiang, Yun (Molecular plant, 2017)
Dynamics of the actin cytoskeleton are essential for pollen germination and pollen tube growth. ACTIN- DEPOLYMERIZlNG FACTORs （ADFs） typically contribute to actin turnover by severing/depolymerizing actin filaments. Recently, we demonstrated that Arabidopsis subclass III ADFs （ADF5 and ADF9） evolved F-actin-bundling function from conserved F-actin-depolymerizing function. However, little is known about the physiological function, the evolutional significance, and the actin-bundling mechanism of these neo- functionalized ADFs. Here, we report that loss of ADF5 function caused delayed pollen germination, retarded pollen tube growth, and increased sensitive to latrunculin B （LatB） treatment by affecting the generation and maintenance of actin bundles. Examination of actin filament dynamics in living cells revealed that the bundling frequency was significantly decreased in adf5 pollen tubes, consistent with its biochem- ical functions. Further biochemical and genetic complementation analyses demonstrated that both the N- and C-terminal actin-binding domains of ADF5 are required for its physiological and biochemical functions. Interestingly, while both are atypical actin-bundling ADFs, ADF5, but not ADF9, plays an important role in mature pollen physiological activities. Taken together, our results suggest that ADF5 has evolved the function of bundling actin filaments and plays an important role in the formation, organization, and maintenance of actin bundles during pollen germination and pollen tube growth.